A population-based registry study on relative survival from melanoma in Germany stratified by tumor thickness for each histologic subtype - Brunssen, Alicia; Brenner, Hermann (Journal of the American Academy of Dermatology, 2019)
Background - Differences in relative survival (RS) of melanoma between histologic subtypes were discussed to be mainly caused by tumor thickness. - Objective - To investigate RS of melanoma, stratified by tumor thickness for each histologic subtype, and identify survival trends. - Methods - With use of cancer registry data on melanoma cases (International Classification of Diseases, 10th Revision, codes C43.0-C43.9) diagnosed in Germany in 1997-2013, 5- and 10-year age-standardized RS stratified by histologic subtype and stratified or standardized by T stage was estimated by standard and modeled period analyses. We restricted 10-year RS analyses to patients younger than 75 years. - Results - We analyzed 82,901 cases. Overall, the 5- and 10-year RS rates were 91.7% and 90.8%, respectively. Prognosis worsened with increasing T stage for all histologic subtypes, but T-stage distribution varied substantially. Survival differences by histologic subtype were strongly alleviated after adjustment for T stage but remained significant. Overall, 5-year RS increased significantly (by 3.8 percentage points) between the periods 2002-2005 and 2010-2013. This increase was no longer seen after adjustment for T stage. - Limitations - Exclusion of cases on account of missing information on T stages, changes in the definition of T stages, and lack of information on screening and treatment limit our analyses. - Conclusion - Differences in RS between histologic subtypes were strongly mediated by tumor thickness. Over time, RS of melanoma increased as a result of changes in T-stage distribution.
Published online September 20, 2018
Gesehen am 05.04.2019